Testing the fair process heuristic in a traffic stop context: Evidence from a factorial study with video vignettes - Solomon, Starr J. (The British journal of criminology, 2021)
We explored whether distributive justice mediated the observed association between procedural justice and legitimacy, as well as cooperation with police. We distributed a 2 × 2 factorial survey to a national online sample of 560 adults. Participants were randomly assigned to view one video vignette of a traffic stop varying the components of procedural justice (decision-making and treatment quality). We used structural equation modelling to test the significance of direct and indirect effects. The results indicated that distributive justice fully mediated the effect of decision-making quality on each outcome and partially mediated the effect of treatment quality on trust and cooperation with police. Theoretical and policy implications are discussed.